How the auditor's judgment made to achieve their goals? - Sukiswo, Helmy Wahyu (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
The study analyzes the influence of goal orientation and self-efficacy on audit judgment, emphasizing the important role in shaping the quality and professionalism of auditor judgment. This study uses a quantitative descriptive method combined with an associative and explanatory approach to analyze the relationship between these variables. Data were collected through a questionnaire survey conducted on 137 auditors working at a Public Accounting Firm in Surabaya. The findings of the study revealed that goal orientation and self-efficacy have a positive and significant impact on audit judgment. These results provide valuable insights that not only improve professional practice but also contribute to the development of guidelines and academic literature in the field of auditing. By understanding these factors, this study aims to support auditors in improving their judgment and decision-making process, which ultimately leads to more accurate and reliable audit results.